Forensic science in the prosecution of illegal drugs cases - Diokno, Maria Socorro I. (2018)
In light of the current ?war on drugs,? forensic science plays a significant role in the prosecution of cases involving illegal drugs to ensure that no innocent persons are ever wrongfully convicted. Prohibited drugs have been a problem in the country since the 1800s. The Philippines has been recognized as ?a significant source of high potency crystalline methamphetamine (shabu) used both domestically and exported to locations in East and Southeast Asia and Oceania.? Yet, the prosecution of those involved with dangerous drugs has not been largely successful. Forensic chemists are crucial to successful drug prosecution but current forensic capabilities could be enhanced. Also, the vital role forensic laboratories play in the area of drug control is under-recognized. Forensic laboratories could ? and should ? provide scientific guidance and advice to strengthen law enforcement, activate early warning systems, enhance regulatory and monitoring capabilities, and develop responsive and effective drug control, prevention, and treatment policies.